Physical and chemical characteristic of stem starch and sheath flour from oil palm tree (Elaeis guineensis) - Syarifah Yusra; Yudi Pranoto; Chairil Anwar; Chusnul Hidayat (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yusra S, Hidayat C, Pranoto Y, Anwar C. 2020. Physical and chemical characteristics of stem starch and sheath flour from oil palm tree (Elaeis guineensis). Biodiversitas 21: 896-902. Replanting old oil palm plantation with a new plant produces a large volume of cleared trees. Yet, the utilization of these by-products is still limited. The objective of this research was to explore and characterize the physicochemical properties of the oil palm stem starch (SS) and sheath flour (SF). SF and SS were extracted by a wet extraction method. Results showed that starch contents of SS and SF (after three times of washing) were 95.56±0.01% and 37.03 ± 0.72%, respectively. Amylose and amylopectin contents of SS were higher than that of sheath starch. Besides, SF contained high protein (19.28% db) and lipid (9.27% db). Protein was also confirmed by FTIR analysis. SF also contained polyphenol. The starch granular was smooth with a clean surface. The granules of SF are classified as very small granules (2-5 µm) while those of SS as small to medium granules (5-25 µm). Polymorph analysis showed that SF and SS had a type-C and B-type, respectively. SF did not have pasting temperature due to the presence of lipid, protein, and polyphenol. Washing of the flour with water decreased protein, lipid and ash contents. It resulted in a decrease in yield about 1.8 times. SS has a pasting temperature of about 71.55°C. Paste viscosity reached a maximum of about 5707 cps. In conclusion, SS that had high viscosity may be used as a thickener and SF may be used for a source of the modified starch to produce such as dextrin and glucose syrup.